Effects of Achasin Protein on Snail (Achatina Fulica) Mucus on Healing Cuts (Vulnus Scissum) in Mice (Mus Musculus) Skin - Triasmara, Wahyu; Berbudi, Afiat; Windria, Sarasati (Journal of Applied Science, Engineering, Technology, and Education, 2023)
Snail mucus Achasin protein is a protein that has important biological functions, besides being intended to prevent evaporation, and assist smooth movement, it is also needed to protect the body from mechanical injuries. This research is expected to increase knowledge about the effect of achasin protein on snail mucus on wound healing and can provide scientific information to the public about the use and benefits of snail mucus as a traditional medicine for healing cuts on the skin of mice ( Mus Musculus ). This type of research is a literature review study that aims to examine the effect of achasin protein on snail mucus ( Achatina Fulica ) on the healing of cuts on the skin of mice ( mus musculus ). Sources of data used in this study used a literature review with relevant sources such as books, official documents, publications, and relevant research results. The results of this study were the achasin protein in snail mucus (Achatina Fulica) can accelerate the healing of cuts (vulnus scissum) on the skin of mice (mus musculus). The content of achasin isolate is also useful as an antibacterial and painkiller. So that people can take advantage of snail slime as an alternative to traditional medicine derived from natural ingredients that have been clinically tested for their efficacy.